Cesarean-section Rates in Brazil from 2014 to 2016: Cross-sectional Analysis Using the Robson Classification - Knobel, Roxana; Lopes, Thiago Jose Pinheiro; Menezes, Mariane de Oliveira; Andreucci, Carla Betina; Gieburowski, Juliana Toledo; Takemoto, Maira Libertad Soligo (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To obtain cesarean-section (CS) rates according to the Robson Group Classification in five different regions of Brazil.Methods A descriptive epidemiological study using data from secondary birth records from the Computer Science Department of the Brazilian Unified Health System (Datasus, in Portuguese) between January 1st, 2014, and December 31st, 2016, including all live births in Brazil.Results The overall rate of CS was of 56%. The sample was divided into 11 groups, and vaginal births were more frequent in groups 1 (53.6%), 3 (80.0%) and 4 (55.1%). The highest CS rates were found in groups 5 (85.7%), 6 (89.5%), 7 (85.2%) and 9 (97.0%). The overall CS rate per region varied from 46.2% in the North to 62.1% in the Midwest. Group 5 was the largest obstetric population in the South, Southeast and Midwest, and group 3 was the largest in the North and Northeast. Group 5 contributed the most to the overall CS rate, accounting for 30.8% of CSs.Conclusion Over half of the births in Brazil were cesarean sections. The Midwest had the highest CS rates, while the North had the lowest. The largest obstetric population in the North and in the Northeast was composed of women in group 3, while in the South, Southeast and Midwest it was group 5. Among all regions, the largest contribution to the overall CS rate was from group 5.
Keywords: cesarean section; vaginal birth after cesarean section; obstetric delivery; repeat cesarean section; induced labor